Who they have become: Peruvian migrants and memories of home, motherhood and violence. Issue 4 (3rd April 2022) - Muñoz, Solange
Abstract: Through the personal narratives of four women who migrated from different cities in Peru to Buenos Aires, Argentina in the mid-nineties and early 2000s, this article explores the long-term impacts of migration, motherhood, and structural and direct violence on women who migrate in order to be able to provide better lives for their children. This article employs a feminist narrative approach to capture the women's life histories and experiences of migration, and positions migration within the broader intersection of motherhood as understood and presented by the women themselves. This article also draws on Johan Galtung's work on structural violence in order to consider the ways in which violence, motherhood and migration intersect in the lives of poor women. Through an analysis of the narratives of the women interviewed, this research specifically asks, how do women rationalize and reconcile their life experiences of migration, motherhood and violence when looking back at their lives and the decisions they have made? By focusing on the multiple conditions of migration, mothering and violence and how women narrate and reflect on their lives, this research analyzes and highlights the complexities of migration, motherhood, family and structural and interpersonal violence, and the ways in which they intersect in intricate and complex ways over time in the lives of poor migrant women.